A microgenetic analysis of teachers' learning through teaching - Yasemin Copur-Gencturk; Sebnem Atabas (SpringerOpen, 2024)
Abstract Background What and how teachers learn through teaching without external guidance has long been of interest to researchers. Yet limited research has been conducted to investigate how learning through teaching occurs. The microgenetic approach (Siegler and Crowley, American Psychologist 46:606-620, 1991) has been useful in identifying the process of student learning. Using this approach, we investigated the development of teacher knowledge through teaching as well as which factors hinder or promote such development. Results Our findings suggest that teachers developed various components of teacher knowledge through teaching without external professional guidance. Further, we found that the extent to which teachers gained content-free or content-specific knowledge through teaching depended on their robust understanding of the concept being taught (i.e., content knowledge), the cognitive demand of the tasks used in teaching, and the lesson structure chosen (i.e., student centered vs. teacher centered). Conclusions In this study, we explored teacher learning through teaching and identified the sources leading to such learning. Our findings underscore the importance of teachers' robust understanding of the content being taught, the tasks used in teaching, and a lesson structure that promotes teachers' learning through teaching on their own.